Annemiek Pas' Zoom transcript, Kenya (Archer’s Post), February 21, 2022 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
Themes: land selling; markets
Keywords: Diseases; Samburu (African people); Vaccination; Schools; Herders; Livestock; Food security; Pastoralist; COVID-19 Pandemic